Main symptoms of osteomioarticular disease presented by supermarket cash operators: an integrative review (Research, Society and Development, 2022)
Introduction: Musculoskeletal disease (MSD) is characterized by damage to muscles, tendons, joints, ligaments, bones, nerves and vascular systems, which can damage the musculoskeletal system or cause functional imbalances. OBJECTIVE: To identify the symptoms of musculoskeletal diseases presented by supermarket cashiers through a literature review. Methodology: This research is an integrative literature review. The inclusion criteria adopted for this integrative literature review were: scientific, cross-sectional, descriptive and quantitative studies; published between 2014 and 2021; in English, Portuguese, Italian or Spanish. Results: The database search totaled 1000 articles. Of this total, 992 articles were excluded as 2 they did not meet the criteria and the remainder met the inclusion criteria and were selected. Of the five (n=5) studies selected for integrative review, five (62.5%) were indexed in the VHL database, one (12.5%) in PubMed, and two (25%) in SciELO. Conclusion: It is understood that cashiers, when performing their function, may report complaints of muscle pain in various regions of the body, thus tending to develop musculoskeletal disorders that interfere with the quality of life of this class of workers.